Teachers' Performance in Indonesian Secondary Schools: Does Motivation Matter? - Amiruddin Hasan; Nurhasanah; Asmaul Husna; A Razak; Martahadi Mardhani (Jurnal EMT KITA, 2022)
A teacher's professional is greatly influenced by internal and external factors. Internal factors are influenced by the motivation that comes from within the teacher's own soul. This study aims to investigate the effect of teacher motivation on the teacher’s performance, especially public senior secondary schools (Sekolah Menengah Atas Negeri, or SMA Negeri) in Banda Aceh, Indonesia. This survey was conducted using a quantitative approach with a sample of 254 teachers. Questionnaires were used to collect data, and the data analysis technique employed was Structural Equation Modelling (SEM). The findings of this study indicate that teacher motivation has a significant effect on improving teacher performance in educational institutions.